Republic of Armenia : Country Procurement Assessment Report - World Bank (World Bank, 2012)
This assessment reviews the current status of public procurement in Armenia and makes recommendations for further improvements. It also provides an update of the Country Procurement Assessment Report (CPAR) carried out in May 2004. The report includes an action plan to assist the Government of Armenia (GoA) in moving the procurement reform agenda forward. The assessment was carried out jointly with the counterpart team appointed by the Minister of Finance. The major procurement legislation and other procurement-related laws and decrees, and documents were analyzed and interviews were conducted with procuring entities, suppliers, contractors, consulting firms, civil society, and government officials. The benchmarking report provides a reference point for the GoA to monitor and measure improvements in the public procurement system, and to formulate a capacity development plan to move towards a sound procurement system that leads to economy and efficiency in public expenditure. Donors can use these results to develop strategies for assisting in procurement capacity building and to mitigate risks in their individual operations. In order to further broaden the perspective on the public procurement functions in Armenia and also to focus on certain specific areas of concern, case studies have been carried out on public procurement in health and transport sectors. In light of the GoA interest in introducing Electronic Government Procurement (e-GP), the team has also prepared a special study on the subject, using the readiness assessment guide of the multilateral development banks' e-GP working group. Case studies have also been prepared on anti-corruption measures, and public-private partnership, given the importance of these topics to public procurement.